Integrating Preconception Health into Routine Reproductive Health Services of Ghana: A Qualitative Study Among University Students - Patience Fakornam Doe; Thomas Hormenu; Nancy Innocentia Ebu Enyan (Tehran University of Medical Sciences, 2022)
Objective: The preconception health (PCH) strategy provides a unique opportunity to reduce risk factors for adverse reproductive outcomes before pregnancy. However, many reproductive-aged individuals continue to miss opportunities to improve their health before pregnancy occurs. This study, qualitatively explored strategies required for integrating PCH promotion interventions into routine reproductive health services from university students' perspectives. Materials and methods: We conducted eight mixed-gender focus group discussions (FGDs) with students in eight schools and faculties in the University from March 2019 to June 2019. Audio-taped data were transcribed verbatim and analyzed manually using inductive content analysis. Results: Three major themes emerged from the analysis of transcripts: interpersonal behavior change strategies, institutional policy directives, public policy interventions, and three main categories with eight sub-categories. The study showed that PCH promotion awareness campaigns, context-relevant service delivery initiatives, institutional and public policy directives are critical approaches for the delivery and uptake of PCH interventions. Participants also recommended prepayment schemes, walk-in services, mobile PCH clinics, and PCH incorporation into university curricula as context-specific strategies for PCH promotion among university students. Conclusion: PCH promotion could be feasible as an integral component of routine reproductive health services for university students. However, multi-level interventions at the student, health service, and institutional levels are necessary to increase awareness and facilitate the request and delivery of PCH services.